Automatic Mapping and Monitoring of Marine Water Quality Parameters in Hong Kong Using Sentinel-2 Image Time-Series and Google Earth Engine Cloud Computing - Kwong, Ivan H. Y.; Wong, Frankie K. K.; Fung, Tung (Frontiers in Marine Science, 2022)
Continuous monitoring of coastal water qualities is critical for water resource management and marine ecosystem sustainability. While remote sensing data such as Sentinel-2 satellite imagery routinely provide high-resolution observations for time-series analysis, the cloud-based Google Earth Engine (GEE) platform supports simple image retrieval and large-scale processing. Using coastal waters of Hong Kong as the study area, this study utilized GEE to (i) query and pre-process all Sentinel-2 observations that coincided with in situ measurements; (ii) extract the spectra to develop empirical models for water quality parameters using artificial neural networks; and (iii) visualize the results using spatial distribution maps, time-series charts and an online application. The modeling workflow was applied to 22 water quality parameters and the results suggested the potential to predict the levels of several nutrients and inorganic constituents. In-depth analyses were conducted for chlorophyll-a, suspended solids and turbidity which produced high correlations between the predicted and observed values when validated with an independent dataset. The selected input variables followed spectral characteristics of the optical constituents. The results were considered more robust compared to previous works in the same region due to the automatic extraction of all available images and larger number of observations from different years and months. Besides visualizing long-term spatial and temporal variabilities through distribution maps and time-series charts, potential anomalies in the monitoring period including algal bloom could also be captured using the models developed from historical data. An online application was created to allow novice users to explore and analyze water quality trends with a simple web interface. The integrated use of remotely-sensed images, in situ measurements and cloud computing can offer new opportunities for implementing effective monitoring programs and understanding water quality dynamics. Although the obtained levels of accuracies were below the desired standard, the end-to-end cloud computing workflow demonstrated in this study should be further investigated considering the cost and computational efficiency for timely information delivery.